Characterization of mechanical properties of hybrid natural fibre reinforced polymer composite - Goh G.B.; Isa M.R.; Zaroog O.S. (American Institute of Physics Inc., 2023)
Natural fibre reinforce polymer composite is gaining attention from researchers worldwide due to its potential as a replacement for synthetic fibre. Its main properties which are environmental-friendly and lightweight make is suitable to be used in many industries such as automotive industry. However, it has low mechanical properties compared to synthetic fibre composite. Hence, to improve its mechanical properties, researchers started to hybridised natural fibre which has proven that this method maximise the mechanical properties of natural fibre composite. This paper investigated the mechanical properties of hybrid pineapple/kenaf fibre reinforced polymer composite with three different fibre loading which are, 3%, 6% and 9%. The method of fabrication is solvent casting method and the matrix used is epoxy resin. The results obtained shows that, for impact strength and hardness, higher fibre loading has higher impact strength and hardness. In the other hand, for tensile test, lower fibre loading has higher tensile strength. 2021 Author(s).